An assessment of students' mobile self-efficacy, readiness and personal innovativeness towards mobile learning in higher education in Malaysia - Mahat, Jazihan; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan (Elsevier, 2012)
Mobile learning, or M-learning, has become a new educational paradigm, gaining popularity especially at institutions of higher learning in Malaysia. Using the latest technology in M-learning, students are able to choose when and where they wish to learn anything. The main aim of this study was to assess learners’ self-efficacy, readiness and personal innovativeness towards Mobile learning. This study also examined the relationship between learners’ self- efficacy and readiness towards M-learning with learners’ perception of the effectiveness of M-learning. The respondents in this study were 137 trainee teachers who had enrolled in various education programs at the Faculty of Educational Studies, University Putra Malaysia. The findings of this study indicated that the respondents had a high level of personal innovativeness and mobile readiness. However, their level of mobile self-efficacy was only moderate.